Folic acid protects against isoniazid-induced liver injury via the m6A RNA methylation of cytochrome P450 2E1 in mice - Jiang, Lan; Ni, Ya; Zhao, Cong; Gao, Dexin; Gai, Xiaochun; Xiong, Ke; Wang, Jinyu (Frontiers in Nutrition, 2024)
Background: Cytochrome P450 2E1 (CYP2E1) converts isoniazid (INH) to toxic metabolites and is critical in INH-induced liver injury. The aim is to investigate the effect of folic acid (FA) on CYP2E1 and INH-induced liver injury. Methods: Male Balb/c mice were used. The mice in the control group only received an AIN-93M diet. The AIN-93M diet was supplemented with 0.66 g INH/kg diet for the mice in the INH and FA groups. The mice in the FA group were treated with additional 0.01 g FA/kg diet. The one-carbon cycle metabolites, the expressions of CYP2E1 and the DNA and RNA methylation levels were detected to reveal the potential mechanism. Results: FA treatment significantly reduced the alanine aminotransferase level and alleviated the liver necrosis. The mRNA and protein expressions of CYP2E1 were significantly lower in the FA group than those in the INH group. The N6-methyladenosine RNA methylation level of Cyp2e1 significantly increased in the FA group compared with the INH group, while the DNA methylation levels of Cyp2e1 were similar between groups. Additionally, the liver S-adenosyl methionine (SAM)/S-adenosyl homocysteine (SAH) was elevated in the FA group and tended to be positively correlated with the RNA methylation level of Cyp2e1. Conclusion: FA alleviated INH-induced liver injury which was potentially attributed to its inhibitory effect on CYP2E1 expressions through enhancing liver SAM/SAH and RNA methylation.